2020
DOI: 10.1186/s12936-020-03317-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis of propeller domain of k13 gene in Plasmodium ovale curtisi and Plasmodium ovale wallikeri isolates original infection from Myanmar and Africa in Yunnan Province, China

Abstract: Background: Eighteen imported ovale malaria cases imported from Myanmar and various African countries have been reported in Yunnan Province, China from 2013 to 2018. All of them have been confirmed by morphological examination and 18S small subunit ribosomal RNA gene (18S rRNA) based PCR in YNRL. Nevertheless, the subtypes of Plasmodium ovale could not be identified based on 18S rRNA gene test, thus posing challenges on its accurate diagnosis. To help establish a more sensitive and specific method for the dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…After screening the full texts, 200 articles were excluded due to the following reasons: 135 not related to species, 17 genetic studies unrelated to P. ovale spp., 15 review articles, 14 case reports or case series, 10 methodology studies, 4 studies using the same participants, 2 letters, 1 with full-text that could not be retrieved, 1 with data that could not be extracted and 1 systematic review. Finally, a total of 36 studies 5 15 , 23 , 25 , 26 , 28 – 32 , 34 , 35 , 39 – 53 were found to meet the eligibility criteria and thus included in the present analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening the full texts, 200 articles were excluded due to the following reasons: 135 not related to species, 17 genetic studies unrelated to P. ovale spp., 15 review articles, 14 case reports or case series, 10 methodology studies, 4 studies using the same participants, 2 letters, 1 with full-text that could not be retrieved, 1 with data that could not be extracted and 1 systematic review. Finally, a total of 36 studies 5 15 , 23 , 25 , 26 , 28 – 32 , 34 , 35 , 39 – 53 were found to meet the eligibility criteria and thus included in the present analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…by Sutherland et al 25 , and 2020. The majority of included studies (14/36, 38.9%) were conducted in African countries (1 in Angola 9 , 1 in Equatorial Guinea 26 , 2 in Ethiopia 5 , 8 , 2 in Gabon 43 , 51 , 1 in Ghana 15 , 1 in Kenya 46 , 1 in Namibia 44 , 2 in the Republic of Congo/Congo 26 , 42 , 2 in Senegal 6 , 7 and 1 in Uganda 26 ), Asian countries (9 in China 12 , 14 , 32 , 35 , 39 , 49 , 50 , 52 , 53 , 2 in India 10 , 11 , 1 in Bangladesh 41 , 1 in Myanmar 12 and 1 in Thailand 13 ), Europe (3 in Italy 29 31 , 2 in France 23 , 45 , 2 in Spain 47 , 48 , 2 in the United Kingdom 25 , 34 and 1 in Germany 40 ) and Northern America (1 in Canada 28 ). Most of the included studies 23 , 25 , 28 , 30 – 32 , 34 , 35 , 39 , 40 , 45 , 47 – 50 , 52 , 53 (19/36, 52.8%) reported indigenous cases of malaria caused by P. ovale curtisi or P. ovale wallikeri , and the remaining studies (17/36, 47.2%) reported imported cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations